Physio morphological plasticity of rice (Oryza sativa L.) genotypes exposed to water-stress - Manikanta, CH L. N.; Beena, R.; Stephen, Roy; Manju, R.V.; Viji, M.M.; Alex, Swapna (Journal of Tropical Agriculture, 2020)
Water stress conditions alter the normal plant equilibrium and lead to a series of morphological, physiological and biochemical as well as molecular changes in plants affecting growth and productivity. An experiment was conducted at the Department of Plant Physiology, College of Agriculture, Kerala Agricultural University during 2018-19 with to evaluate the physio-morphological plasticity of rice genotypes under water stress. Plants of six rice genotypes, Nagina 22, Karutha Modan (Ptb 29), Chuvanna Modan (Ptb 30), Annapoorna (Ptb 35), Jyothi (Ptb 39) and Swetha (Ptb 57) were maintained at 100 % and 50 % FC soil moisture in a rainout shelter. Physio morphological observations were recorded at the booting stage and Nagina 22, Karuthamodan and Chuvannamodan, being tolerant genotypes, exhibited better plasticity in terms of physiological and root traits towards water stress whereas, Annapoorna, Jyothi and Swetha failed to respond. In the tolerant genotypes, there was no significant reduction in Relative Water Content (RWC), Cell Membrane Stability (CMS), and Specific Leaf Area (SLA) whereas, there was a significant increase in the growth of root parameters. Biomass partitioning data revealed allocation of dry matter towards root under stress compared to control condition.